2023
DOI: 10.3390/vetsci10090561
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Responses to Fecal Microbiota Transplantation in Cats with Chronic Digestive Issues

Connie A. Rojas,
Zhandra Entrolezo,
Jessica K. Jarett
et al.

Abstract: There is growing interest in the application of fecal microbiota transplants (FMTs) in small animal medicine, but there are few published studies that have tested their effects in the domestic cat (Felis catus). Here we use 16S rRNA gene sequencing to examine fecal microbiome changes in 46 domestic cats with chronic digestive issues that received FMTs using lyophilized stool that was delivered in oral capsules. Fecal samples were collected from FMT recipients before and two weeks after the end of the full cour… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 80 publications
0
6
1
Order By: Relevance
“…Interestingly, the fecal microbiomes of FMT recipients were not significantly predicted by clinical signs; that is, dogs with diarrhea did not have fundamentally different microbiomes from dogs with vomiting and/or constipation. This contrasts findings from a recently published study conducted in cats that took oral capsule FMTs for their chronic digestive issues [ 26 ]. That study reported that the fecal microbiomes of cats with diarrhea differed from the fecal microbiomes of cats with constipation and/or vomiting.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Interestingly, the fecal microbiomes of FMT recipients were not significantly predicted by clinical signs; that is, dogs with diarrhea did not have fundamentally different microbiomes from dogs with vomiting and/or constipation. This contrasts findings from a recently published study conducted in cats that took oral capsule FMTs for their chronic digestive issues [ 26 ]. That study reported that the fecal microbiomes of cats with diarrhea differed from the fecal microbiomes of cats with constipation and/or vomiting.…”
Section: Discussioncontrasting
confidence: 99%
“…No two FMT participants had identical preFMT or postFMT microbiomes. Similarly, a recently published study in cats also reported individual-specific microbiome responses to oral FMTs [ 26 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Changes in the bacterial composition of the gut microbiota were also described, with a decrease in the abundance of Clostridium perfringens and an increase in the abundance of Blautia spp., Ruminococcus torques and Ruminococcus gnavus ( Lee et al, 2022 ). Oral fecal microbiota transplant capsules were prospectively administered to 46 pet cats with chronic gastrointestinal signs, leading to partial stool donor bacterial engraftment ( Rojas et al, 2023 ). The fecal microbiota of responders tended to become more similar to the fecal microbiota of healthy cats ( Rojas et al, 2023 ).…”
Section: Modulation Of the Gut Microbiota In Cats With Cementioning
confidence: 99%